2018
DOI: 10.1108/mf-12-2016-0350
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric price responses to stock addition to and deletion from the Athens Stock Exchange Index

Abstract: Purpose The purpose of this paper is to investigate the response of investors to the announcements on the inclusion and exclusion of companies from the FTSE-ASE 20 index. Design/methodology/approach Data on the inclusion and exclusion of companies from the FTSE-ASE 20 index in the period 2000-2012 were used. The authors performed an event study analysis using a constant return model and a market model. Two different measures of aggregated abnormal returns, namely the cumulating abnormal returns and the buy-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…This result shows that the market reacts more to negative information, in which case the exit of the company from the Index is perceived as a negative signal of the company's inability to meet the criteria set by each Index. The results of this study are in line with research by Papachristou et al (2018) who found that the market reaction to the shares of companies that came out of the FTSE-ASE20 Index (Athens Stock Exchange) was more prominent than the company's stocks that entered the index. Specifically, Papachristou et al (2018) found that a significant negative market reaction lasted longer (longer) than a positive market reaction on companies that entered into the Index (took place in a short time).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This result shows that the market reacts more to negative information, in which case the exit of the company from the Index is perceived as a negative signal of the company's inability to meet the criteria set by each Index. The results of this study are in line with research by Papachristou et al (2018) who found that the market reaction to the shares of companies that came out of the FTSE-ASE20 Index (Athens Stock Exchange) was more prominent than the company's stocks that entered the index. Specifically, Papachristou et al (2018) found that a significant negative market reaction lasted longer (longer) than a positive market reaction on companies that entered into the Index (took place in a short time).…”
Section: Discussionsupporting
confidence: 90%
“…Papachristou et al (2018) found that companies leaving the index experienced significant negative reactions and even these negative reactions lasted more than 15 days. As for the case of companies included in the index, Papachristou et al (2018) found that there is a positive market reaction but takes place in the short term. In this regard, the announcement of a change of company listings in an index is seen as a signal of confidence for investors over the prospects of the company's financial performance in the future.…”
Section: Efficient Market Hypothesismentioning
confidence: 98%
See 3 more Smart Citations